Bis 4-hydroxy-N '-(4-methoxy-2-oxido-benzylidene-kappa O-2)benzohydrazidato-kappa O-2,N ' cadmium(II) dimethyl sulfoxide disolvate - Lair, N.M.; Ng, Seik Weng; Ali, Hapipah Mohd (International Union of Crystallography, 2009)
The metal atom in the title compound, [Cd(C15H13N2O4)(2)]center dot-2C(2)H(6)OS, is twice O,N,O'-chelated by two symmetry-related Schiff base ligands to define a trans-N2O4 octahedral geometry. Each anion occupies meridional sites of the octahedron; the metal atom lies on a special position of site symmetry 2. The dimethyl sulfoxide molecule is a hydrogen-bond acceptor to the -NH- unit, and O-H center dot center dot center dot O hydrogen bonds link molecules into a supramolecular chain.